Uma extensão do teorema de Barta e aplicações geométricas - Silva, José Deibsom da (2010)
We present an extension to Barta's Theorem due to G. P. Bessa and J. F. Montenegro and we show some geometric applications of the obtained result. As first application, we extend Chang's lower eigenvalue estimates of the Laplacian in normal geodesic balls. As second application, we generalize Cheng-Li-Yau's eigenvalue estimates to a minimal submanifold of the space forms.